Piezoelectric biomaterials for providing electrical stimulation in bone tissue engineering: Barium titanate - Huagui Huang; Kaizhong Wang; Xiangyan Liu; Xin Liu; Jinzuo Wang; Moran Suo; Hui Wang; Shuang Chen; Xin Chen; Zhonghai Li (Journal of Orthopaedic Translation)
With the increasing clinical demand for orthopedic implants, bone tissue engineering based on a variety of bioactive materials has shown promising applications in bone repair. And various physiological cues, such as mechanical, electrical, and magnetic stimulation, can influence cell fate and participate in bone regeneration. Natural bone has a piezoelectric effect due to the non-centrosymmetric nature of collagen, which can aid in cell adhesion, proliferation and differentiation, and bone growth by converting mechanical stimuli into electrical stimuli. Piezoelectric materials have the same piezoelectric effect as human bone, and they are able to deform in response to physiological movement, thus providing electrical stimulation to cells or damaged tissue without the need for an external power source. Among them, Barium titanate (BaTiO3) is widely used in tumor therapy, tissue engineering, health detection and drug delivery because of its good biocompatibility, low cytotoxicity and good piezoelectric properties. This review describes the piezoelectric effect of natural bone and the characteristics of various types of piezoelectric materials, from the synthesis and physicochemical characteristics of BaTiO3 and its application in biomedicine. And it highlights the great potential of BaTiO3 as piezoelectric biomaterials in the field of bone tissue engineering in anticipation of providing new ideas and opportunities for researchers.The translational potential of this article: This review systematically discusses barium titanate, a bioactive material that can mimic the piezoelectric effect of natural bone tissue, which can intervene in the regenerative repair of bone by providing a sustained electrical microenvironment for bone repair scaffolds. This may help to solve the current problem of poor osteogenic properties of bioactive materials by utilizing barium titanate.